'And yet, everything we do is usually based on the English': sailing the mare incognitum of Star Trek's transatlantic double consciousness with Horatio Hornblower. (October 2016) - Rabitsch, Stefan
Abstract : While pitched and sold to television executives as being a space western – which of course it was not – the world of Star Trek was intentionally and systematically modelled on the British golden age of sail as found in Napoleonic sea fiction. This article offers a synoptic and decidedly transatlantic critique of Star Trek, exposing a hidden British maritime world embedded beneath a veneer of 'Americanness'. In doing so, it re-addresses and offers a corrective to the question of why Star - Trek -as-space-western has guided most Star Trek scholarship. It will show why it makes sense to re-historicise Star Trek not only as a product of the 1960s, but also as a distillate of impulses that originated in the late 1940s and 1950s. Remapping the origins of Star Trek along these lines reveals how and why it was only logical that the world-building of Star Trek was intentionally and continuously modelled on the eighteenth century British naval world. This maritime endowment is embedded in five maritime dimensions that shape the ontology of Star Trek 's future world in space. They encompass operational discourses, nomenclature, visual and conceptual aesthetics, and character archetypes as well as rituals, traditions and an entire maritime milieu.